2017
DOI: 10.1002/hsr2.20
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofOxalis barrelieriL. (Oxalidaceae) aqueous extract on diarrhea induced byShigella dysenteriaetype 1 in rats

Abstract: Aim: Oxalis barrelieri is a medicinal plant commonly used in Cameroon, for the treatment of many diarrheal diseases. The antibacterial properties of O barrelieri aqueous extract (WOb) against Shigella dysenteriae type 1 were investigated in vitro and in vivo.Methods: Antibacterial activity was evaluated in vitro by disc diffusion method and by macrodilution method. S dysenteriae type 1 at a dose of 1.2 × 10 9 CFU was administrated orally to rats to induce shigellosis. For 6 consecutive days, diarrheic rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In vitro , Crinum jagus extract showed concentration-dependent antibacterial activities. The MIC/MBC ratio was lower than 4 and could thus indicate a bactericidal activity [ 26 ]. This activity was further confirmed by the reduced bacterial load observed with in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , Crinum jagus extract showed concentration-dependent antibacterial activities. The MIC/MBC ratio was lower than 4 and could thus indicate a bactericidal activity [ 26 ]. This activity was further confirmed by the reduced bacterial load observed with in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Oxalis barrelieri is a medicinal plant used to treat certain pathologies such as diabetes [13] and diarrhea [7,8]. In this study, the objective was to evaluate the toxic effects of this plant on biological systems, particularly in the liver and kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Enoch et al [6] reported that administration of 500 mg/kg and 1000 mg/kg aqueous and ethanolic extracts of O. barrelieri on Sprague-dawley rats produced significant reductions of glycemia in both non-diabetic and diabetic rats. A decoction of the entire plant is used for the treatment of diarrhea [7,8]. O. barrelieri is rich in phenols, flavonoïds, tannins, alkaloids and saponins [9].…”
Section: Introductionmentioning
confidence: 99%
“…They can be of infectious origins (bacterial, viral, parasitic or fungal), inflammatory, tumoral or medicinal (antibiotics). Infectious diarrhea is caused by bacteria such as Salmonella, Shigella [2] and Entomopathogenic colibacilli [3]; by viruses such as parvoviruses, rotaviruses, reoviruses [4], or by parasites such as amoebae and helminths [5]. These infections increase in case of lack of safe water for various household chores and for consumption.…”
Section: Introductionmentioning
confidence: 99%